HUBUNGAN OVERDISTENSI UTERUS DENGAN PERDARAHAN POST PARTUM DI RSUD BENGKULU TAHUN 2011 - Putri, Suzana Fabella (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Haemorhagia are the main factor of dying mother. According to the Survei Kesehatan Rumah Tangga (SKRT) in 2007, dying mother causes by haemorhagia reached opver 60%. Haemorhagia post partum which was happened in RSUD M. Yunus Bengkulu in the year 2011 had a significant number which are 208 cases. This researched have a purpose to known the relation between overdistention uterus and haemorhagia post partum in RSUD M. Yunus Bengkulu in the year 2011.Research conducted analytic survey with case control study design. The research was conducted in July until August 2012.The population are the mother who giving a birth which number 2.244 with quantity of sample are 416 with a ratio of 1:1 and separated by 208 sample taken as total sampling for the cases and 208 sample taken as systematic random sampling for the control. Data analysis has served in univariat and bivariat analysis. The result showed from 208 haemorhagia post partum cases, small percentage (20,7%) of mother had makrosomia babies and a small portion (12,5%) of mother who had gamelli babies and small amount (6,2%) of mother got polyhidramnion case. The result of statistical test found a significant association between overdistention uterus with haemorhagia post partum. Expected for health workers to be more carefull and to have early identitifed of haemoraghia post partum risk factors so that can make great decision.